ANALISIS KEPUASAN KONSUMEN TERHADAP KONSUMSI MINYAK GORENG CURAH DI PASAR PINASUNGKULAN KAROMBASAN - Yunetris Sarendaren; Leonardus R. Rengkung; Joachim N.K. Dumais; Vicky R.B. Moniaga (COCOS, 2015)
ABSTRACT  Yunetris Sarendaren. Analysis of Consumer Satisfaction Of Bulk Cooking Oil Consumption In Pinasungkulan Market Karombasan Manado (under the guidance of Dr. Ir. Leonardus R. Rengkung, ME as a Chairman, Ir. Joachim Dumais, ME as a Member, Ir. Vicky R.B Moniaga, MSi as Members).  The objective of this research is to determine the level of customer satisfaction of the cooking oil products in the city of Manado in terms of price, product, location and service in Pinasungkulan Market Karombasan Manado. Data collection was conducted for 3 months from January to March 2015. The data used in this study were primary data and secondary data. Primary data were obtained by using questionnaire to respondent. Secondary data was collected from all business owners/store cooking oil involved in this study that were the traders in the Pinasungkulan Market Karombasan Manado.  The research result showed that the price and products offered by 13 stores around the Pinasungkulan Market Karombasan Manado is affordable therefore the public or consumers are satisfied with the price of cooking oil and product sold in the market. On the other side the place and service of Pinasungkulan Market Karombasan Manado were still needed to improved.  Keyword : Cooking Oil Consumption, and level of satisfaction